Implementasi Layanan Bimbingan Kelompok Untuk Meningkatkan Sikap Asertif Peserta Didik Kelas Xi Smks Taman Siswa Medan - Andriani Andriani; Uli Makmun Hasibuan; Aulia Latifa; Valencia Marito Hutabarat (Kampus Akademik Publiser, 2026)
One of the important social skills that children must have to face various demands of social life in school and community environments is assertive behavior. Assertive students are able to express their ideas, feelings, and opinions firmly without violating the rights of others. The purpose of this study is to describe how group counseling services are used to help 11th-grade students at SMKS Taman Siswa Medan become more assertive. This study uses a descriptive qualitative methodology and collects data through group counseling transcripts, service implementation reports, and documentation studies of the Service Implementation Plan (RPL). According to the research findings, group counseling services go through four stages: development, transition, core activities, and termination. Students actively participate in conversations, share their experiences, and voice their thoughts on assertive behavior throughout the service process. Students demonstrate a deeper understanding of the concept of assertiveness, courage in expressing their ideas, and the ability to politely refuse unwanted offers after participating in the service. The research conclusion indicates that group counseling services are a useful strategy to help students improve their social skills, particularly in terms of becoming more assertive.